Identification of Key Actors in Mangroves Plantation using the MACTOR Tool: Study in DKI Jakarta - Tjondroargo Tandio; Cecep Kusmana; Akhmad Fauzi; Endang Hilmi (Jurnal Sylva Lestari, 2023)
Considering the benefits of mangrove forest areas and their ability to support the success of sustainable development, this study aimed to determine the attitudes of stakeholders in the Special Capital Region of Jakarta (DKI Jakarta) toward the existence of mangrove areas in the North Coast of  Jakarta.  Surveys and data collection were conducted through focus group discussions and interviews. The results showed that the key actors in the development of mangrove areas in DKI Jakarta are the Ministry of Environment and Forestry of the Republic of Indonesia, the Department of Environmental Services of DKI Jakarta Province, the Government of DKI Jakarta Province, the Government of North Jakarta City, and the Regional House of Representatives of DKI Jakarta. In addition, other stakeholders, such as the developer, park bureau, regional development and ecotourism, were included as relay variables. In addition, the study identified the entrepreneurs, fishermen, farmers, and ponds as the dependent variables, while the industries, civil society, and warehousing as the independent variables. This study identified several options for the development of mangrove areas in DKI Jakarta, such as utilizing potential areas that have not been planted with mangroves for business area development, property development, national strategic project program, and mangrove plantation. The results of this study are expected to help policymakers develop policies for mangrove development in DKI Jakarta. Keywords: DKI Jakarta, MACTOR, mangrove forest, key actors